The experiences of spirituality among adults with mental health difficulties: a qualitative systematic review. (2020) - Milner, K.; Crawford, P.; Edgley, A.; Hare-Duke, L.; Slade, M.
Abstract: Aims: Despite an increasing awareness of the importance of spirituality in mental health contexts, a 'religiosity gap' exists in the difference in the value placed on spirituality and religion by professionals compared with service users. This may be due to a lack of understanding about the complex ways people connect with spirituality within contemporary society and mental health contexts, and can result in people's spiritual needs being neglected, dismissed or pathologised within clinical practice. The aim of this qualitative systematic review is to characterise the experiences of spirituality among adults with mental health difficulties in published qualitative research. Methods: An electronic search of seven databases was conducted along with forward and backward citation searching, expert consultation and hand-searching of journals. Thirty-eight studies were included from 4944 reviewed papers. The review protocol was pre-registered (PROSPERO:CRD42017080566). Results: A thematic synthesis identified six key themes: Meaning-making (sub-themes: Multiple explanations; Developmental journey; Destiny v . autonomy), Identity, Service-provision, Talk about it, Interaction with symptoms (sub-themes: Interactive meaning-making; Spiritual disruption) and Coping (sub-themes: Spiritual practices; Spiritual relationship; Spiritual struggles; Preventing suicide), giving the acronym MISTIC. Conclusions: This qualitative systematic review provides evidence of the significant role spirituality plays in the lives of many people who experience mental health difficulties. It indicates the importance of mental health professionals being aware of and prepared to support the spiritual dimension of people using services. The production of a theory-based framework can inform efforts by health providers to understand and address people's spiritual needs as part of an integrated holistic approach towards care.